Epidemiology of Methicillin-Resistant Staphylococcus aureus Bloodstream Coinfection Among Adults With Candidemia in Atlanta, GA, 2008–2012. (27th August 2015) - Reno, Jessica; Doshi, Saumil; Tunali, Amy K.; Stein, Betsy; Farley, Monica M.; Ray, Susan M.; Jacob, Jesse T.
Abstract : BACKGROUND: Patients with candidemia are at risk for other invasive infections, such as methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infection (BSI). OBJECTIVE: To identify the risk factors for, and outcomes of, BSI in adults with Candida spp. and MRSA at the same time or nearly the same time. DESIGN: Population-based cohort study. SETTING: Metropolitan Atlanta, March 1, 2008, through November 30, 2012. PATIENTS: All residents with Candida spp. or MRSA isolated from blood. METHODS: The Georgia Emerging Infections Program conducts active, population-based surveillance for candidemia and invasive MRSA. Medical records for patients with incident candidemia were reviewed to identify cases of MRSA coinfection, defined as incident MRSA BSI 30 days before or after candidemia. Multivariate logistic regression was performed to identify factors associated with coinfection in patients with candidemia. RESULTS: Among 2, 070 adult candidemia cases, 110 (5.3%) had coinfection within 30 days. Among these 110 coinfections, MRSA BSI usually preceded candidemia (60.9%; n=67) or occurred on the same day (20.0%; n=22). The incidence of coinfection per 100, 000 population decreased from 1.12 to 0.53 between 2009 and 2012, paralleling the decreased incidence of all MRSA BSIs and candidemia. Thirty-day mortality was similarly high between coinfection cases and candidemia alone (45.2% vs 36.0%, P =.10). Only nursing home residence (odds ratio, 1.72 [95% CI, 1.03–2.86]) predicted coinfection. CONCLUSIONS: A small but important proportion of patients with candidemia have MRSA coinfection, suggesting that heightened awareness is warranted after 1 major BSI pathogen is identified. Nursing home residents should be targeted in BSI prevention efforts. Infect. Control Hosp. Epidemiol. 2015;36(11):1298–1304